DEVELOPMENT OF THEMATIC TEXTBOOKS FOR CLASS IV PRIMARY SCHOOLS - Rezi S, Faeza; Fadly, Yuafriza (Jurnal Ilmu Pendidikan Ahlussunnah, 2024)
Education is the key to developing a nation's civilization. The process of implementing education is one form of manifestation of human culture that is dynamic and full of development. Changes and developments in education are things that should happen in line with cultural changes. The thematic learning process is a tendency to return to the initial idea that children will learn better when the environment is created naturally. Learning will be more meaningful if children experience what they are learning, not knowing it. Thematic learning is learning that is designed based on certain themes. Likewise with integrated integration that integrates various subjects in one particular learning theme. This type of research is included in the type of Research and Development. The research and development methods can be used to produce and test the effectiveness of products from a particular study. To be able to produce certain products, research is used in the form of needs analysis and to test the effectiveness of the product so that it can function properly. The development of thematic textbooks for Class IV Elementary School was developed using a 4-D development model (four D Models), namely defining, planning, developing and disseminating. The results were valid, practical and effective. Therefore, it can be used as a learning guide for teachers and students at school.